Vaccination as an Equaliser? Evaluating COVID-19 Vaccine Prioritisation and Compensation. (9th December 2022) - Günther, Christian; Tonti, Lauren; Domenici, Irene
Abstract: This article assesses the equity of COVID-19 vaccination programmes in three jurisdictions that have historically taken different approaches to the institutionalisation of equity considerations. The Sars-Cov-2 pandemic has thrown into sharp relief persistent societal inequalities and has added novel dimensions to these problems. Certain groups have proved particularly vulnerable, both in terms of infection risk and severity as well as the accompanying social fallout. Against this background the implementation of 'objective' vaccination programmes may seem like a great leveller, addressing the disparate risks that are tied to social determinants of health and the pandemic behemoth. However, implementing vaccination programmes in an equitable manner is itself essential for the realisation of such a vision. This article undertakes a comparative analysis of the English, Italian, and American jurisdictions and critically assesses two aspects of their vaccination frameworks: (i) the prioritisation of groups for vaccination and (ii) the nature of public compensation schemes for those who have suffered vaccine-related injuries. It examines whether and to what extent these measures address the inequalities raised by COVID-19 and the role of the law in this pursuit.